Asynchronous responses of soil carbon dioxide, nitrous oxide emissions and net nitrogen mineralization to enhanced fine root input. (January 2016) - Hu, Xiaokang; Liu, Lingli; Zhu, Biao; Du, Enzai; Hu, Xueyang; Li, Peng; Zhou, Zhang; Ji, Chengjun; Zhu, Jiangling; Shen, Haihua; Fang, Jingyun
Abstract: Global environmental changes can remarkably alter the amount of fine root litter inputs to the soil; these inputs affect soil CO2 and N2 O emissions and net N mineralization processes by changing C and N supply to microorganisms. However, how these C and N processes respond to the amount of fine root litter input is yet not known. In this study, a year-long incubation experiment was conducted to investigate the impacts of changes in fine root litter biomass input on soil respiration, N2 O emissions, and net N mineralization. Soil samples were obtained from forests of four biomes (boreal, temperate, subtropical, and tropical), and each sample was amended with fine roots from two species (either native tree species or maize roots) with four levels of root biomass input. The cumulative CO2 emissions increased linearly with root input levels, regardless of soil and root litter types. Soil respiration responded strongly to root inputs within the first 100 days and then leveled off. Root inputs retarded soil N2 O emissions and net N mineralization, and the length of delay increased with root input levels, except for temperate and subtropical soils amended with tree roots, for which N2 O emission dynamics were not altered by root input. Tree roots retarded net N mineralization more intensively than maize roots except for the tropical tree roots. Cumulative N2 O emissions increased linearly with root input levels in only some soil type–root species–root input level combinations. Taken together, our results suggest that increased fine root biomass production might result in a linear increase of soil C loss via heterotrophic respiration, indicating that the first-order kinetic functions that have been widely used in the soil C models are still valid for predicting C mineralization rates in response to the changes in the amount of root litter inputs. Fine roots in their initial decomposition stage could be the predominant sources of soil N2 O emissions in some but not all terrestrial ecosystems. However, increased fine root input might retard net N mineralization, which might disrupt the temporal pattern of ecosystem N cycling, and thus have important consequences on plant N supply and growth. Highlights: Root impacts on soil CO2 and N2 O efflux and net N mineralization were studied. CO2 emission increased linearly with root input levels. Roots in their initial decomposition stage could be strong N2 O sources. CO2 and N2 O efflux response to altered fine root input is asynchronous. Increasing root input prolonged the time required for soil net N mineralization.